ANALISIS FAKTOR YANG MEMENGARUHI KEMATANGAN KARIR PADA SISWA SMK DI WALANTAKA, KOTA SERANG - Novita Azizah; Arga Satrio Prabowo; Putri Dian Dia Conia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Career maturity is a sign of an individual's success in completing their career development tasks. This study aims to obtain an overview of the factors that influence students' career maturity (Survey research on vocational high school students in Walantaka, Serang City). This study uses a quantitative research type with a survey method. The selected subjects were 303 vocational high school students in Walantaka, Serang City aged 15 to 17 years. Data collection used a questionnaire containing 32 items. The research instrument was a questionnaire containing 32 statements about factors that influence students' career maturity based on Donald E. Super's theory. The results of this study are an overview of the career maturity of vocational high school students in Walantaka, Serang City in general, which is in the moderate category. This is indicated by the results of the frequency distribution, namely students who are in the moderate category are 55%, the high category is 45%, and the low category is 0%. Factors that influence students' career maturity consist of bio-social factors, environment, personality, vocational, and adolescent achievement.